Christian Muslim relations. a bibliographical history - Thomas, David 1948-; Chesworth, John; Azumah, John Alembillah. (The History of Christian-Muslim Relations, 2015)
Christian-Muslim Relations. A Bibliographical History, volume 7 (CMR 7), covering Central and Eastern Europe, Asia, Africa and South America in the period 1500-1600, is a continuing volume in a general history of relations between the two faiths from the seventh century to the early 20th century. It comprises introductory essays and the main body of detailed entries which treat all the works, surviving or lost, that have been recorded. These entries provide biographical details of the authors, descriptions and assessments of the works themselves, and complete accounts of manuscripts, editions, translations and studies. The result of collaboration between numerous leading scholars, CMR 7, along with the other volumes in this series, is intended as a basic tool for research in Christian-Muslim relations. Section editors: Clinton Bennett, Luis F. Bernabe Pons, Lejla Demiri, Martha Frederiks, John-Paul Ghobrial, David Grafton, Alan Guenther, Abdulkadir Hashim, Şevket Küçükhüseyin, Emma Loghin, Gordon Nickel, Claire Norton, Peter Riddell, Umar Ryad, Davide Tacchini, Moussa Serge Hyacinthe Traore, Carsten Walbiner